Identification of Corynebacterium amycolatum and Other Nonlipophilic Fermentative Corynebacteria of Human Origin - Wauters, Georges (American Society for Microbiology, 1998)
Four identification tests, proposed in addition to conventional methods, were evaluated with 320 fermentative nonlipophilic Corynebacterium strains: growth at 20°C, glucose fermentation at 42°C, alkalinization of sodium formate, and acid production from ethylene glycol. These tests were highly discriminant. Corynebacterium amycolatum displayed a unique profile, allowing it to be distinguished from similar species, such as C. xerosis, C. striatum, and C. minutissimum.